Quercetin Inhibits Pulmonary Arterial Endothelial Cell Transdifferentiation Possibly by Akt and Erk1/2 Pathways. (27th March 2017) - Huang, Shian; Zhu, Xiulong; Huang, Wenjun; He, Yuan; Pang, Lingpin; Lan, Xiaozhong; Shui, Xiaorong; Chen, Yanfang; Chen, Can; Lei, Wei
Abstract : This study aimed to investigate the effects and mechanisms of quercetin on pulmonary arterial endothelial cell (PAEC) transdifferentiation into smooth muscle-like cells. TGF- β 1-induced PAEC transdifferentiation models were applied to evaluate the pharmacological actions of quercetin. PAEC proliferation was detected with CCK8 method and BurdU immunocytochemistry. Meanwhile, the identification and transdifferentiation of PAECs were determined by FVIII immunofluorescence staining and α -SMA protein expression. The related mechanism was elucidated based on the levels of Akt and Erk1/2 signal pathways. As a result, quercetin effectively inhibited the TGF- β 1-induced proliferation and transdifferentiation of the PAECs and activation of Akt/Erk1/2 cascade in the cells. In conclusion, quercetin is demonstrated to be effective for pulmonary arterial hypertension (PAH) probably by inhibiting endothelial transdifferentiation possibly via modulating Akt and Erk1/2 expressions.